The effect of different drinking water in culture medium on feces microbiota diversity - Kun Zhou (IWA Publishing, 2021)
The human gut harbors trillions of microbes, which are extremely important to the health of the host. However, the effect of drinking water on gut microbiota has been poorly understood. In this study, we explored the response of BALB/c mice gut bacterial community (feces) to the different types of drinking water, including commercial bottled mineral water (MW), natural water (NW), purified water (PW) and tap water (TW). Feces were cultured with brain heart infusion broth dissolved in four types of drinking water. 16S rRNA gene analysis was performed. Our results reveal that the microbiota composition is different among culturing with four types of drinking water. As the culture time increases, the number of OTUs significantly decreased, except under the aerobic condition of MW. Under aerobic conditions on the 5th day, the considerable differences of alpha diversity index are found between MW and three others, and these are the most unique taxa in the MW group. Importantly, the LEfSe analysis discovers that the Bacteroidetes taxa dominate the differences between MW and the other water types. Our findings demonstrate that the mineral water as a culture medium may lead to a progressive increase of the gut microbiota diversity by providing the growth convenience to Bacteroidetes. HIGHLIGHTS The gut microbiota composition was different by culturing with different types of drinking water.; Mineral water leads to a progressive increase of the microbiota diversity and provides the growth convenience to Bacteroidetes.;